Cellular lattice cores of sandwich panels fabricated by additive manufacturing: Effect of dimensions and relative density on mechanical behaviour. (May 2023) - Pereira, Diogo; Alves, Frederico PD; Reis, Luis; Leite, Marco; Deus, Augusto M; Sardinha, Manuel; Vaz, M Fatima
Sandwich panels have a wide field of applications from aerospace to automotive industries. These panels are formed by a core and two layers, having the geometry of the core an important role in its mechanical properties. While the most common cores have hexagonal honeycomb structures, there is a recent trend to replace them with other cellular structures based on truss or lattice arrangements. Previous studies on modified atomic-based lattices reached the conclusion that modified body and face-centred parallelepiped, with vertical struts, denoted by the body- and face-centred parallelepiped with struts in z -axis, provided higher stiffness and absorbed energy with low weight, compared with the conventional design. These promising findings have motivated a further comprehensive investigation of this type of structure. The aim of the present study is to get the body- and face-centred parallelepiped with struts in z-axis structure that provides the highest stiffness and absorbed energy, in comparison with a previous work of the current authors, by changing its dimensions and relative density. To accomplish this purpose body- and face-centred parallelepiped with struts in z -axis lattices with three relative densities, namely, 0.25, 0.30 and 0.35 and with truss radii of 0.8, 0.92 and 1.1 mm were designed, respectively. Samples were printed by additive manufacturing of polylactic acid. The two face sheets (skins) and the core of the panel were manufactured altogether. The mechanical behaviour of the sandwich panels was assessed by three-point bending tests both experimentally and in numerical simulations with finite element analysis. A good correlation between experiments and numerical results was achieved. Simulation results revealed that the highest values of strength, stiffness and absorbed energy were obtained for the combination of the lowest relative density with the highest truss radius. A failure analysis revealed two failure modes, namely, cohesive failure and face sheet failure. Results indicate that the dimensions of the struts and the relative density affect the mechanical performance and the failure mode of the panels.